1029 EVEN LIMITED GERIATRICIAN INVOLVEMENT REDUCES LENGTH OF STAY FOR ALL-AGE ACUTE GENERAL SURGERY PATIENTS. (14th June 2022) - Luo, R; Hudson, M; Cepeda, V; Reese, G; Sritharan, G; Peck, G; Morgan, C; Koizia, L; Fertleman, M
Abstract: Background: More than half of patients undergoing emergency general surgery are older than 651. The Emergency Laparotomy and Frailty (ELF) study identified that frail patients (CFS ≥5) were vulnerable to adverse outcomes and longer hospital stays and should be reviewed by a geriatrician2. The 2021 National Emergency Laparotomy Audit (NELA) found that only 27% were reviewed by a geriatrician1. Local problem A local hospital had no routine geriatrician input to perioperative care of older people admitted under the care of general surgeons. Method/Intervention: In one month prior to intervention, we noted CFS recorded once and a geriatrician involved in only 3 patients over the age of 65 (n = 35). We introduced a service comprising twice-weekly geriatrician-led multi-disciplinary team (MDT) meetings of all-age patients followed by selected patient ward rounds. This equated to 2.5 Programmed Activity's (PA) per week. After another month we measured the number of patients having CFS recorded, those who had geriatrician involvement and length of stay. We also surveyed members of the MDT. Results: All 31 patients aged over 65 received geriatrician input with 93.5% having a CFS recorded. Length of stay of all-age patients (n = 75) was reduced from 12.8 to 8.8 days, with the most significant reduction of 6.5 days in over 65's (16.7 to 10.2); >200 bed days saved for older people. The MDT comments included: 'improved MDT communication', 'early identification of discharge barriers' and 'pro-active approach'. Conclusion: NELA highlights that consistent geriatrician input remains generally poor. Even a limited geriatrician-led service can be highly effective at guaranteeing review of appropriate patients in line with recommendations from NELA. Alongside targeted patient review geriatricians can support and lead decision making of all-age patients. This cost-effective strategy can reduce length of stay for young and old alike and gained excellent feedback from the MDT.